A toolbox for tuberculosis diagnosis: an Indian multicentric study (2006-2008): microbiological results. - Philippe H Lagrange; Satheesh K Thangaraj; Rajeshwar Dayal; Alka Despande; Nirmal K Ganguly; Enrico Girardi; Beenu Joshi; Kiran Katoch; Vishwa M Katoch; Manoj Kumar; Vemu Lakshmi; Marc Leportier; et al. (PLoS ONE, 2012)
BACKGROUND: The aim of this multicentric prospective study in India was to assess the value of several microbiological tools that contribute to the diagnosis of tuberculosis (TB) according to HIV status. METHODS: Standard microbiological tools on individual specimens were analyzed. RESULTS: Among the 807 patients with active TB, 131 were HIV-infected, 316 HIV-uninfected and 360 had HIV-unknown status. Among the 980 non-active TB subjects, 559 were at low risk and 421 were at high risk of M. tuberculosis (Mtb) exposure. Sensitivity of smear microscopy (SM) was significantly lower in HIV-infected (42.2%) than HIV-uninfected (75.9%) (p = 0.0001) and HIV-unknown pulmonary TB patients (61.4%) (p = 0.004). Specificity was 94.5% in non-TB patients and 100% in health care workers (HCW) and healthy family contacts. Automated liquid culture has significantly higher diagnostic performances than solid culture, measured by sensitivity (74.7% vs. 55.9%) (p = 0.0001) and shorter median time to detection (TTD) (12.0 vs. 34.0 days) (p = 0.0001). Specificity was 100% in HCW and cured-TB patients, but was lower in non-TB patients (89%) due to isolation of Mycobacteria other than tuberculosis (MOTT). TTD by both methods was related to AFB score. Contamination rate was low (1.4%). AccuProbe hybridization technique detected Mtb in almost all culture-positive specimens, but MOTT were found in 4.7% with a significantly higher frequency in HIV-infected (15%) than HIV-uninfected TB patients (0.5%) (p = 0.0007). Pre-test classification significantly increased the diagnostic value of all microbiological tests in pulmonary TB patients (p<0.0001) but to a lesser degree in extrapulmonary TB patients. CONCLUSIONS: Conventional microbiological tools led to results similar to those already described in India special features for HIV-infected TB patients included lower detection by SM and culture. New microbiological assays, such as the automated liquid culture system, showed increased accuracy and speed of detection.